ANAPC10 expression predicts poor prognosis in oral squamous cell carcinoma and promotes tumor growth via the PI3K/AKT/mTOR pathway - Jing Fang; Yanhao Duan; Yongle Qiu; Shanshan Liu; Xue Bai; Hong Cai; Meijie Zhang; Wei Liu (Discover Oncology)
Abstract Oral squamous cell carcinoma (OSCC) is associated with high morbidity and mortality, emphasizing the need for early detection through advanced biomarkers and non-invasive methods. This study analyzed Anaphase Promoting Complex Subunit 10 (ANAPC10) mRNA expression across various cancers using multi-platform tools to assess its diagnostic potential and clinical relevance. We developed a prognostic model linking ANAPC10 expression to survival outcomes using TCGA and GTEx data, and constructed a protein–protein interaction network via GeneMANIA. Functional studies, including cell culture and various assays, demonstrated that ANAPC10 is highly expressed in OSCC and correlates with poor prognosis. ANAPC10 was found to be involved in key pathways, including NF-κB signaling and cell cycle regulation. Knockdown experiments revealed that reducing ANAPC10 expression led to decreased cell proliferation, migration, and invasion, as well as inhibition of the PI3K/AKT/mTOR signaling pathway. These findings suggest that ANAPC10 is a promising biomarker for OSCC and a potential therapeutic target Clinical Trial Number: Not applicable.